Gender and leadership in trade unions - Kirton, Gill (Routledge research in employment relations, 2013)
Reflecting the increased attention to gender and women in the field of employment relations, there is now a growing international literature on women and trade unions. The interest in women as trade unionists arises partly from the fact that women comprise 40 percent of trade union membership in the USA and over 50 percent in the UK. Further, despite considerable overall union membership decline in both the UK and USA, more women than men are joining unions in both countries. Recognition of the importance of women to the survival and revival of trade union movements has in many cases produc.